PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PADA INDUSTRI PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2010 "“ 2012 - B51110016, Tri Wahyuni (Jurnal KIAFE, 2014)
The objectives of this research are to analyze the impact of Intellectual Capital on firm"™s financial performance that measured by Return On Asset (ROA). Data for this research is from financial report of banking industry that listed in Indonesia Stock Exchange (IDX) from 2010 "“ 2012. The model that used to measure the Intellectual Capital is model that was made by Pulic, that is Value Added Intellectual Coefficient (VAIC). Pulic model separately consist of Value Added Capital Employed (VACA), Value Added Human Capital (VAHU) and Structural Capital Value Added (STVA). In this research, Statistical Product and Service Solutions (SPSS) was used to examine the relationship between VAIC and banking industry"™s financial performance. The result of this research show : (1) Intellectual Capital has an impact on banking industry"™s financial performance. (2) Value Added Capital Employed (VACA) has a positive impact and significant on Return On Asset. (3) Value Added Human Capital (VAHU) has a positive impact and significant on Return On Asset. (4) Structural Capital Value Added (STVA) has a negative impact and significant on Return On Asset. Keyword: Intellectual Capital, Return On Assets (ROA), Value Added Intellectual Coefficient (VAIC), Banking Industry.